What alternative supplements are prominent between some of female athletes?: A systematic review - Katmawanti, S.; Hanim, S.; Sharoni, S. K. A.; Fauzi, R.; Samah, D. A.; Wahyuni, O. S. (Journal of Physical Education and Sport, 2022)
Athletes of all abilities, particularly elite athletes, are encouraged to use sports nutrition strategies that improve mental and physical performance while also supporting good health. These strategies include eating a well-balanced diet with enough energy to meet the macronutrient and micronutrient requirements of training and competition, maintaining optimal body mass (BM) and composition, and implementing specific nutritional strategies before, during, and after training to improve performance. Female athletes experience injuries compared to male athletes so there needs to be good and appropriate injury prevention management for female athletes. This research method is a literature review with several stages. Eligibility Criteria, Information sources and search, Study Selection, Data collection Process. From 125 publications 100 articles remained after the first selection, which was adjusted for duplicates. After screening the abstracts, 70 were excluded. The full texts of 230 articles were screened using eligibility criteria. Finally, 30 studies on female/women athletes subjects were accepted for the qualitative analysis. In the articles that have been observed, several types of supplements used by female athletes appear, supplements, including iron supplements, calcium, types of drinks that contain high protein, packaged drinks that contain high creatinine, caffeine, melatonine, vitamin D, New Zealand Blackcurrant, sodium phospate. Despite the fact that female athletes outnumber male athletes in certain sports, literature on nutrient consumption and, in particular, supplement intake in female athletes is lacking. Even though female athletes are one of the groups prone to malnutrition, it is necessary to manage food intake while properly monitoring how to take supplements so that conditions in which female athletes experience malnutrition do not occur.